Reconstruction of the proto-type basin and tectono-paleogeography of Tarim Block in the Mesozoic - Li, Xiang; Chang, Haining; Huang, Shaoying; Luo, Caiming; Duan, Yunjiang; Zhang, Hao; Xia, Jinkai; Zhong, Ziqi; Wei, Lunyan (Frontiers in Earth Science, 2023)
The reconstruction of the proto-type basin and tectono-paleogeography of the Tarim Basin during the Mesozoic is crucial for hydrocarbon exploration, particularly for identifying hydrocarbon source rocks. This study reconstructs the position, thickness, and distribution of the original stratigraphy, the shortening amount by structural deformation, and the distribution of sedimentary facies in each Mesozoic period using paleomagnetic data, residual stratigraphy data, seismic profiles, and lithofacies distribution. During the Triassic period, a syn-collision thrust fault structure formed in the southern Tarim Block due to the successive collision of the Tianshuihai-Bayankara terrane, North Qiangtang terrane, and South Qiangtang terrane with the Tarim Block. The sedimentary strata mainly distributed in the Northern Depression and Kuqa Depression, and their sedimentary centers continuously moved northward. In the Early-Middle Jurassic, faulted basins representing post-collision extensional structures developed on the margins of the Tarim Block. In the Late Jurassic, the Tarim Block was compressed, and the faulted basin transformed into a depressional downwarped basin with red coarse clastic sediments due to the collision of the Amdo-Dongkacuo microcontinent with the Tarim Block. In the late Early Cretaceous, the collision between the Lhasa Block and the Tarim Block caused the entire uplift of the Tarim Block, which stopped accepting deposition except for the deposition of marine facies in the southwestern Tarim Basin influenced by a large-scale transgression event. The complex evolution of the Paleo-Tethys and Neo-Tethys Oceans during the Mesozoic significantly influenced the sediment distribution and structural features of the Tarim Basin.